BIBLIOMETRIX STUDY OF DIGITAL MARKETING RESEARCH ON THE TIKTOK SOCIAL MEDIA PLATFORM - Febriyanti Dwi Mahfudloh; Umar Burhan; Rachmad Ilham (Journal Informatic, Education and Management (JIEM), 2026)
This study aims to map the development of scientific literature on digital marketing on the TikTok platform using a bibliometric approach. Research data were obtained from the Scopus database covering the period from 2018 to 2024, resulting in 847 documents that met the established inclusion and exclusion criteria. The analysis was conducted using Bibliometrix R-Package and VOSviewer software to identify publication trends, the most productive authors and institutions, the most influential journals, country contributions, and thematic research clusters. The results indicate that publications in this field experienced rapid growth, peaking in 2022 with 231 documents. China dominates global publication contributions with 214 documents, while the United States records the highest average citation rate of 28.83 per document. The Journal of Retailing and Consumer Services was identified as the most influential journal with 48 articles and an h-index of 24. The dominant topics identified include influencer marketing, purchase intention, and brand awareness. This study confirms that TikTok-based digital marketing research has evolved into a dynamic multidisciplinary field that still holds considerable research gaps to be further explored by the global academic community.